Boosting Engagement and Reducing Anxiety: The Impact of Quizizz on Science Learning in Elementary Classrooms - Husain, Andi Musthafa; Maryani, Ika; Fauzia, Safira Nur; Hartanto, Dody; Muarifah, Alif (The Indonesian Institute of Science and Technology Research, 2025)
Science education in elementary schools often encounters challenges related to technological accessibility, particularly when integrating digital tools such as Quizizz for assessment. Institutional policies, including restrictions on mobile phone usage, are typically implemented to maintain student concentration and prevent technological distractions. While shifting students' mindset toward new learning methods can be challenging, school support can foster a high-quality learning environment that benefits all students. This study aims to explore the implementation and impact of the Quizizz game on students' anxiety levels during elementary science evaluations. Using a quantitative quasi-experimental design with a Pretest-Posttest Control Group approach, data were collected through questionnaires involving all 43 sixth-grade students. The results indicate that the use of Quizizz as a learning evaluation tool significantly improved student engagement in the experimental group. Overall, 52% of the experimental group fell into the